Essays on the effects of oil price shocks on exchange rates and the economy of Saudi Arabia - Al Rasasi, Moayad Hussain (Kansas State University, 2016)
This dissertation consists of three essays examining the consequences of oil price shocks on exchange rates and the economy of Saudi Arabia. In the first essay, we examine the impact of oil prices on the US dollar (USD) exchange rate in the flexible monetary model framework. We find evidence, based on the impulse response function analysis from the VEC model, suggesting the negative association between oil prices and the USD against 12 currencies. Furthermore, the results from out-of-sample forecasts indicate that oil prices play an essential role in improving the forecasting power of the monetary model of exchange rate determination. In the second essay, we analyze how G7 real exchange rates and monetary policy respond to oil supply, aggregate demand, and oil-specific demand shocks initiated by Killian (2009). Our evidence confirms that aggregate demand and oil specific demand shocks are associated with the depreciation of the real exchange rate for five countries whereas oil supply shocks lead to the depreciation of real exchange rate in four countries. Likewise, we find the monetary policy responds significantly only to aggregate demand and oil specific demand shocks in three countries while the monetary policy responds to real exchange rate shocks in four countries. In the third essay, we investigate the differential effects of oil shocks, developed by Killian (2009), on industrial production, inflation, and the nominal exchange rate of Saudi Arabia. The reported evidence shows that industrial production responds positively only to oil supply shocks. Likewise, we find evidence indicating that there is a positive impact of aggregate demand shocks on inflation. On the other hand, we find evidence suggesting that oil supply and demand shocks are associated with the nominal exchange rate depreciation.
Keywords: Economics